Reflection-in-action as a collective process: findings from a study in teaching students of negotiation. Issue 1 (2nd January 2017) - Johnston, Shannon; Fells, Ray
Abstract: Real-time reflection-in-action is a critical capability for effective practitioners, just as the more common reflection-on-action is critical for learning. Reflective practice is typically regarded as an individual activity. However, to be an effective negotiator involves real-time reflection-in-action . Results from a Masters-level Negotiation unit show that reflection in negotiation contexts is emergent rather than sudden, is collective, and typically occurs in a break from the negotiation action. We develop the work of Schön and Yanow and Tsoukas to propose a framework of reflection-in-action that better fits the interactive context of negotiation and explore some implications for the teaching of negotiation and other similar professional situations.